APPLICATION OF SIMPLE DISPLACEMENT MONITORING SYSTEM FOR ROCK/SOIL MOVEMENT AT BINUNGAN MINE OPERATION OF PT. BERAU COAL - ZULFAHMI ZULFAHMI (Puslitbang tekMIRA, 2007)
This monitoring result illustrates the real slope stability and could be used as datat for back analysis to obtain the real shear strength (c and ö).Study of monitoring system application to detect soil/rock movement at mine slope was conducted bya team from tekMIRA in 2006. The location of trial run was Binungan Mine Operation, PT. Berau Coal. The team used combinations of simple, accurate and relatively low cost monitoring equipment consists of radio modem, data logger and potential trans- ducer. Potential transducers were connected to the observation points using a wire line. When the movement occurs along the mine slope, the wire line will cause a difference potentiometer voltage. The results show a good value of linearity with value of r-square between 0.964 and 0.98